Studi Bibliometrik Eksplorasi Tren Glamping 2019-2024 - Laksmi, Gratia Wirata; Dewi, Triana Rosalina; Tarigan, Emenina; Oktadiana, Hera; Ingkadijaya, Rahmat (Jurnal Ilmiah Pariwisata, 2024)
Glamping is a nature-based accommodation alternative popular in various parts of the world. Glamping is developing rapidly in all parts of the world, but research on the keyword glamping has yet to be widely discussed. Researchers use bibliometric analysis methods to present visualizations and knowledge about glamping. Researchers searched for SCOPUS and SINTA indexed articles published between 2019-2024 via Publish or Perish (PoP) software application. There were 245 published documents found, and only 26 published documents successfully passed the exception selection. Researchers formulated two problem statements: "What are the research trends on glamping?" and "Is the topic of glamping amenable to further research?". This research aims to determine trends in glamping research from 2019-2024 and to determine the development of glamping research to provide recommendations for glamping research in the future. Researcher found ten keyword trends on glamping: glamping , camping, tourism ,  sustainable tourism, accommodation ,  experience, accommodation environment,   glamping tourism ,  word of mouth,  and  tourist resources. The study found that Glamping is a stimulating topic because the glamping trend has become relevant to the tourist profile after the COVID-19 pandemic . Keywords: glamping, glamping trends, nature-based accommodation, alternative accommodation, bibliometric study